Brexpiprazole in patients with schizophrenia: overview of short- and long-term phase 3 controlled studies. Issue 5 (16th November 2016) - Marder, Stephen R.; Hakala, Mika Juhani; Josiassen, Mette Krog; Zhang, Peter; Ouyang, John; Weiller, Emmanuelle; Weiss, Catherine; Hobart, Mary
Abstract : Objective: Review efficacy, safety, and tolerability of brexpiprazole in patients with schizophrenia in short- and long-term phase 3 studies. Methods: Patients experiencing a current exacerbation of schizophrenia received brexpiprazole in two fixed-dose (2 and 4 mg), 6-week, placebo-controlled studies, one flexible-dose (2–4 mg), 6-week, placebo-control and active reference study, and one fixed-dose (1–4 mg), 52-week, placebo-controlled maintenance study. Results: The efficacy of brexpiprazole was demonstrated in the two short-term fixed-dose studies with statistically significant improvements from baseline in Positive and Negative Syndrome Scale (PANSS) total score compared with placebo. In the flexible-dose short-term study, treatment with brexpiprazole resulted in numerically greater improvements in PANSS total score than with placebo that approached statistical significance ( p =0.056). A meta-analysis of these short-term studies showed a mean change in PANSS total score of −20.1, reflecting a clinically meaningful reduction in symptoms. In the maintenance study, brexpiprazole had a beneficial effect relative to placebo on time to exacerbation of psychotic symptoms/impending relapse ( p <0.0001). For all studies, brexpiprazole demonstrated clinically meaningful treatment effects on the Personal and Social Performance scale. Brexpiprazole had a favourable safety profile, with a relatively low prevalence of activating and sedating side effects. Weight gain in the short-term studies was ~1 kg greater than placebo. No safety concerns were observed with brexpiprazole in laboratory values, electrocardiogram, or vital signs. Conclusions: Overall, the results indicate brexpiprazole, used either short-term or as part of a long-term maintenance treatment programme, is an efficacious therapy option in adults with schizophrenia and has a favourable safety/tolerability profile.